Cross‐cutting digital technologies as a tool to counteract sanctions restrictions - S.S. Krasnykh (Векторы благополучия: экономика и социум)
Relevance. Growing importance of technological independence in the context of global economic and political challenges. The imposed sanctions restrictions lead to the transformation of economic processes, which include restricted access to external markets, investments, technologies and innovations. Under such conditions, the search for effective solutions that can minimize the effects of the imposed sanctions and accelerate the transition to independent and high‐tech production becomes a priority task. Aim. To analyze the use of cross‐cutting digital technologies to counteract sanctions pressure in the Russian Federation. Methods. Analysis of scientific works devoted to the assessment of the use of modern technologies in various fields and analysis of the impact of sanctions restrictions on the Russian economy; generalization and synthesis of the author's idea of using cross‐cutting digital technologies as a tool to counteract sanctions restrictions. Results. The analysis of the possibilities of using artificial intelligence, machine learning, the Internet of things, electronic technologies, additive technologies and quantum computing as tools to counter sanctions restrictions shows the following feature – these information technologies have minimal potential for reducing restrictive measures. They can significantly increase economic and technological independence, accelerate the production localization and enhance data security. The practical application of these solutions has already demonstrated positive results in a number of industries, and their development in the Russian Federation can significantly mitigate the effects of the imposed sanctions, ensuring technological sovereignty and long‐term sustainability of the economy